Synthesis of novel triazole hybrids with pyrene, fluorene, and biphenyl groups and evaluation of their antimycobacterial activity - Goyal Akshi; Bhandari Meena (Heterocyclic Communications, 2025)
The synthesis of 1,2,3-triazoles, which are acting as promising pharmacophores with strong biological activity, is the focus of our work. Three obscure streaks of hybrid molecules with a 1,2,3-triazole nucleus have been synthesized by us. Compounds are synthesized in two steps: first, an azide is formed from its amine equivalent, next 1,2,3-triazole ring is formed utilizing azide-alkyne click chemistry. The obtained yields range from fair to good. After testing, it is discovered that the compounds 1c, 2a, 2c, 3a have good antibacterial properties and compounds 2b, 3a have promising antifungal properties. The compounds are found to be soluble in ethanol, ethyl acetate. The primary difficulty we encountered was with cyclopropane as the reaction needed to be carried out under reflux at 100°C, and its boiling point is 51°C.